Gender realities local and global - Segal, Marcia Texler, 1940-; Demos, Vasilikie P. (Advances in gender research, 2005)
The ten papers in "Gender Realities: Local and Global" document the types of work in which women engage, and gender equity issues they face. They show both the importance of considering the uniqueness of cultural contexts for understanding and resolving problems and how global interdependence affects local gender realities. The papers fall into two broad and overlapping categories: gender, work and development, and gender and discrimination. Papers related to particular settings focus on the resettlement of villagers in Lesotho, the development of welfare policies in Puerto Rico, the experiences of fishery workers in Newfoundland and of immigrants to Maritime Canada, decisions made by retired couples in the United States, problems faced by academics in Finnish universities, classroom interaction in Canadian law schools, and attitudes of and about school children in Nepal. Other papers examine the role of gender in the informal economy worldwide and the globalization of sexual harassment. Authors based in the United States, Canada and Finland employ a variety of qualitative and quantitative research methods including extensive field work, interviews, surveys, and literature reviews. An introduction by the editors relates the papers to one another and to broad gender themes. Each paper includes an extensive reference list and the volume index allows readers to track specific topics from one paper to the next.